TAKDIR DAN KEBEBASAN MENURUT FETHULLAH GÃœLEN - Haderi, Anang (Fakulta Ushuluddin dan Humaniora Universitas Islam Negeri Walisongo Semarang, Indonesia, 2014)
Abstract:Destiny and free will is one of issues in Islamic theology which is still discussed by Moslem theologian up to now. This discussion has yielded some streams with its argumentation respectively. Included who intense to discuss this issue is muá¸¥ammad Fethullah GÃ¼len. At a glance, he offers to explain the issue in his own way without following one of the streams. He introduces some key terms, like ImÄm MubÄ«n, KitÄb MubÄ«n, Lauá¸¥ Maá¸¥fÅ«áº“, Formal or Theoretical Destiny, actual destiny. Terms are GÃ¼lenâ€™s exclusive. The article will elaborate the explaination of GÃ¼len relating to the destiny and free will. The purpose is to map what is he follows the streams or he has interpretation in himself. For this reason, I will spread out briefly views of theologian before, i.e. these streams of Muâ€™tazili, al-Asyâ€™arite, MatÅ«ridite Samarkand dan MatÅ«ridite BukhÄrÄ. By this way it will be seen clearly where is the position of GÃ¼len and what is contribution of his thinking. Abstrak: takdir dan kebebasan adalah isu teologi Islam yang masih diperbincangkan oleh para teolog hingga sekarang. Perdebatan ini telah melahirkan berbagai aliran dengan penÂ¬dapatÂ¬nya masing-masing. Termasuk yang juga intens memÂ¬bahas isu ini adalah Muá¸¥ammad Fethullah GÃ¼len. Sekilas, ia berusaha menjelaskan isu ini dengan caranya sendiri tanpa mengikuti salah satu aliran tersebut. Ia mengenalkan beÂ¬berapa istilah kunci, seperti ImÄm MubÄ«n, KitÄb MubÄ«n, Lauá¸¥ Maá¸¥fÅ«áº“, takdir formal, takdir teoritis, dan takdir aktual. Istilah-istilah ini merupakan khas GÃ¼len. Tulisan ini akan mengelaborasi penjelasan GÃ¼len mengenai takdir dan keÂ¬bebasÂ¬an tersebut. Tujuannya adalah memetakan apakah ia mengikuti aliran-aliran teologi yang sudah ada ataukah ia mempunyai pemaknaan sendiri terÂ¬hadap persoalan ini. Untuk alasan ini, penulis akan meÂ¬maparÂ¬kan secara singkat pendapat para teolog sebelumnya, yakni aliran-aliran Muâ€™taziÂ¬lah, al-Asyâ€™ariyah, MÄtÅ«ridiyah Samarkand dan MÄtÅ«ridiyah BukhÄrÄ. Dengan cara ini akan terlihat dengan jelas di manaÂ¬kah posisi GÃ¼len dan apa kontribusi dari pemikirannya itu. Keywords: ImÄm MubÄ«n, KitÄb MubÄ«n, Lauá¸¥ Maá¸¥fÅ«áº“, takdir formal, takdir aktual.